Analisis Perawatan Crane Hoist pada Intake PLTA Maninjau - Rafika Andari; Sitti Amalia; Syafeii Syafeii; Sitti Amalia; Sitti Amalia (Syntax Corporation, 2023)
The purpose of this research is to identify the type of crane hoist and examine the maintenance procedure that must be followed if the PLTA Maninjau Intake Hoist crane sustains damage. At the Maninjau hydropower facility, two treatments are carried out: routine maintenance and repair maintenance. Preventive maintenance (routine) is frequently performed on the PLTA Maninjau intake hoist crane four times a month / once a week. Corrective type maintenance is performed for transformer and contactor damage because it replaces components. As for pendan damage, only predictive type maintenance is carried out. Initially, each crane equipment was checked, then tested by operating the crane and checking which parts had malfunctioned or were damaged based on their use. If the crane being operated is damaged, then a re-check is carried out on the circuit or on the crane equipment that has failed. If the crane has no problem/damage, it means that the crane is in good condition and the inspection is complete.